Emergency Department Implementation of the Brain Trauma Foundation's Pediatric Severe Brain Injury Guideline Recommendations. Issue 4 (April 2020) - Lumba-Brown, Angela; Totten, Annette; Kochanek, Patrick M.
Abstract : Abstract: The "Guidelines for the Management of Pediatric Severe Traumatic Brain Injury, Third Edition: Update of the Brain Trauma Foundation Guidelines" published in Pediatric Critical Care Medicine in 2019 provides new and updated recommendations applicable to the emergency department management of children with severe traumatic brain injury. Practice-changing takeaways include specific recommendations for administration of 3% hypertonic saline, administration of seizure prophylaxis, and avoiding hyperventilation.